Pertumbuhan Benih Ikan Nila (Oreochromis niloticus) dengan Menggunakan Pakan Komersil yang Diberi Tambahan â€œBakasangâ€ - Mujiono, Faisal; Sampekalo, Julius; Lumenta, Cyska (e-Journal BUDIDAYA PERAIRAN, 2015)
The objectives of research were to evaluate the effect bakasang-supplemented commercial diet on nile tilapia growth and to find the optimum dosage of bakasang to be supplemented in feed. The research was conducted at Laboratory of Nutrition and Fish Feed Technology.Â  Fish weighing 0,9-1,7 g were palced in 15 aquaria at a density of 10 individuals/aquarium. Experimental design was complete randomized design with five treatments namely A (0% bakasang), B (2% bakasang), C (3% bakasang), D (4% bakasang), E (5% bakasang), each with three replications. Fish were fed three times a day as much as 5%/body weight. Growth of fish was observed every week. Research results showed that the lowest absolute growth, relative growth and feed efficiencyÂ  were observed in treated with 0% bakasang (ÃªG=20.44 g; GR=148.08%; dan NEP=58.06%) while the highest was obtained in fish treated with 4% bakasang (ÃªG=35,55 g; GR=262.17%; NEP=80.53%).Â  Analysis of variance displayed the use of bakasang significantly affect absolute growth, relative growth. It was concluded that feed supplemented with 4% bakasang gave better absolute growth, relative growth and feed efficiency as compared to other feed. Â  Keywords: growth, â€œbakasangâ€, absolute growth, relative growth, feed efficiency, Â nile tilapia